A quantitative hydroclimatic context for the European Great Famine of 1315–1317 - Seung H. Baek (Nature Portfolio, 2020)
Exceptionally wet growing seasons, compared to the past 700 years, preceded the European Great Famine of 1315-1317 and are associated with a newly identified hydroclimate pattern, according to analyses of Europe-wide tree ring data.